2018
DOI: 10.1101/261610
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regulation of ATM and ATR by Smarcal1 and BRG1

Abstract: The G2/M checkpoint is activated on DNA damage by the ATM and ATR kinases that are regulated by post-translational modifications. In this paper, the transcriptional coregulation of ATM and ATR by SMARCAL1 and BRG1, both members of the ATPdependent chromatin remodeling protein family, is described. SMARCAL1 and BRG1 colocalize on the promoters of ATM and ATR; downregulation of SMARCAL1/BRG1 results in transcriptional repression of ATM/ATR and therefore, overriding of the G2/M checkpoint leading to mitotic abnor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 62 publications
1
18
0
Order By: Relevance
“…were also found on the promoter of ATM gene (Fig. 2C), once again validating the experimental results obtained in previous studies 26 . Finally, we analyzed the presence of these two proteins on ABC transporters as previously BRG1 has been shown to regulate the expression of these genes in breast cancer cells 7 .…”
Section: The Transcriptomic Profile Of Hela Cells Is Altered On Treatsupporting
confidence: 92%
See 1 more Smart Citation
“…were also found on the promoter of ATM gene (Fig. 2C), once again validating the experimental results obtained in previous studies 26 . Finally, we analyzed the presence of these two proteins on ABC transporters as previously BRG1 has been shown to regulate the expression of these genes in breast cancer cells 7 .…”
Section: The Transcriptomic Profile Of Hela Cells Is Altered On Treatsupporting
confidence: 92%
“…1G). The ATPase activity of these proteins is needed for co-regulating transcription [24][25][26][27] . Also, we had previously shown that cell line resistant to ADAADiN showed decreased ATPase activity of SMARCAL1 and BRG1 that manifested in alterations in the transcriptomic profile of the cells 6 .…”
Section: The Transcriptomic Profile Of Hela Cells Is Altered On Treatmentioning
confidence: 99%
“…In HEK293 and MCF-7, SMARCAL1 positively regulates the expression of BRG1 but BRG1 negatively regulates the expression of SMARCAL1. 62 Biophysical studies using CD spectrophotometer has shown that the ATPase activity of ADAAD is used in remodeling the DNA into a structure that is similar to the conformation adopted by stem-loop DNA in the presence of the protein and ATP. 7,61 The ATPase activity is essential for the remodeling as both the ATPase dead mutant as well as addition of ADAADi, the specific inhibitor of ADAAD, fails to remodel the DNA.…”
Section: Smarcal1 Is a Transcriptional Co-regulatormentioning
confidence: 99%
“…These two proteins are present simultaneously on the promoters of ATM, ATR, DROSHA, DGCR8, and DICER. 62,72 On doxorubicin-induced DNA damage, SMARCAL1 and BRG1 are upregulated. 61,62,72 Furthermore, the occupancy of both SMARCAL1 and BRG1, along with RNAPII, increases at the TSS of these promoters leading to the upregulation of their expression.…”
Section: Smarcal1 and Brg1 Transcriptionally Co-regulate Dna Damagementioning
confidence: 99%
See 1 more Smart Citation